Presence of thyroid nodes in patients with metabolic syndrome in a Peruvian tertiary care hospital - Noriega-Ruiz, Victor (2020)
Objective: To compare the frequency of thyroid node disease (TND) in patients with metabolic syndrome (MS) and in patients without metabolic syndrome in an area with good iodine supply. Materials and methods: This is an analytical comparative casecontrol study performed in paired groups. There were 40 patients with MS and 40 controls attending the Endocrinology service in Cayetano Heredia Hospital in Lima, Peru, who were paired according to age and sex. Weight, height, and blood pressure measurements were taken from clinical records. Abdominal circumference was measured, and the presence of acanthosis nigricans was determined. Lipid profile, baseline blood glucose and TSH were determined. Thyroid ultrasonography was performed in all participants. Thyroid volume values were recorded and thyroid nodes measuring >5-mm were considered as clinically significant. Results: Eighty per cent of the studied population in both groups was women. There were significant differences in tobacco use, acanthosis nigricans, TSH levels, thyroid volume, weight, body mass index, abdominal circumference, diastolic blood pressure, baseline blood glucose, HDL-cholesterol and triglyceride levels between both groups. TND was more frequent in those patients with MS compared to patients with no MS (40% vs. 12.5%, respectively; p= 0.015). The odds ratio (OR) for having thyroid nodes in the presence of MS was 4.66 (95% confidence interval: 1.34–16.24). There were significant differences in thyroid volume for both groups (p= 0.039). Conclusion: In an area with good iodine supply, MS was associated to TND to with an increased thyroid volume.